The effect of radiology services outsourcing on patients’ satisfaction in Tehran city hospitals - Mousavi, H (J Med Life, 2015)
Background: To have a developed society we should have healthy, active, and happy individuals and present that extended healthcare services perform an essential function in increasing the society’s health level. Health in a society includes the society’s, and people comfort with the condition and an assuring the situation that they can live healthily. Also, considering the self-governing plan of hospitals from 1995, the hospital authorities should choose a method of presenting services, and, the hospital is ready to present those activities during its own activities from an economic viewpoint. The current study was done while trying to discover the effect of the Outsourcing of the Radiology Unit on the patients’ satisfaction in hospitals of Tehran. Method: The present research was done in a case-evidence and sectional study. Considering the weight of a month’s references to the Radiology Unit, which included around 1200 individuals, the volume of samples for measuring the frequency of the patients’ satisfaction with the means of Morgan table was similar to 291 individuals. To decrease the error percentage in each hospital we questioned 300 individuals. (n+10) were questioned and the gathered information were examined by what means SPSS application variant 21 and were then studied by climagraph – Smirnoph, Du Whitman – Vitney K tests. Findings: the mean of the patients’ satisfaction of turned over and non-turned over Radiology Unit services were 41.46 and 45, respectively (from the maximum score of 60). A meaningful variation was seen among the patients' Satisfaction in the two hospitals from the analytical viewpoint (p-value<0.001) and there was also a significant difference between the patients’ waiting time (p-value<0.001). The research’s findings showed that the outsourcing has a negative influence on the patients’ satisfaction and the duration of their waiting time. Conclusion: Many times, managers do the outsourcing without considering individual and organizational dimensions and characteristics by just justifying it based on decreasing the expenses. Therefore, it is essential for authorities to consider not only the economic characters but also the individual and human aspects while setting the outsourcing contracts and arrangements.